Aleitamento materno exclusivo por mães vegetarianas e suas possíveis implicações para a criança - Melissa Gershon; Lucca de Faria Santos Amorim; Romero Ribeiro Duque; Alegna Cristiane Medeiros Sobrinho; Rodrigo Moreira Garcia; Luciano Rodrigues Costa (Sociedade Brasileira de Pediatria, 2022)
It is known that the period of life between pregnancy and the childs two years of age is critical for the promotion of growth and development, which makes adequate nutrition essential for the complete potential development of each human being. In this sense, the present study aims to discuss the peculiarities of exclusive breastfeeding up to 6 months of life of the infant by vegetarian mothers and its possible implications for the child. This is a narrative review based on the evaluation of protocols by the Brazilian Vegetarian Society, Brazilian Society of Pediatrics and Society of Pediatrics of São Paulo, as well as articles comprised between 1982 and 2020, available in online databases. Human milk contains lipids, vitamins, minerals, proteins, carbohydrates, immunoglobulin A, interferon, enzymes, and growth modulators. This composition is generally similar when comparing vegetarian and non-vegetarian breast milk, however it differs quantitatively. In view of this, in the case of exclusive breastfeeding by vegetarian mothers, medical evaluation is necessary to determine whether there is a need for nutritional supplementation, especially vitamin B12, iron and omega-3. In cases where breastfeeding is not possible, an alternative is infant formulas based on soy or rice. Recent studies show that the growth and development of children fed through soy or rice-based formulas may be similar to that of infants who received exclusive breastfeeding or formula based on cows milk.